Pengaruh Content Marketing TikTok terhadap Customer Engagement (Studi Kuantitatif pada Akun TikTok SilverQueen Selama Masa Campaign Banyak Makna Cinta) - Athaya Nadjla Azzariaputrie; Fitria Avicenna (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Abstract - Increasingly complex customer needs made businesses must help customers meet these needs, from providing information about brands and products to creating communications that build customer trust and engagement. Content marketing was part of a strategy in the digital marketing era that planned, created, and distributed message content in an attractive way with the aim of attracting target markets and encouraging them to become customers of a brand. This study aimed to examine the effect of content marketing on customer engagement. This study examined content marketing as an independent variable with indicators of reader cognition, sharing motivation, persuasion, decision-making, and factors. The sample in this study amounted to 100 respondents selected by purposive sampling method. The sample in this study were SilverQueen customers aged 18-24 who had commented, liked, or shared the content of the Banyak Makna Cinta campaign video on SilverQueen's TikTok account. All data obtained in this study were analysed using simple linear regression. The results of this study indicated that content marketing had a significant effect on customer engagement with the indicator factor being the most dominant indicator of content marketing.